¿"Obreros de la viña" o savants? Los misioneros de la Compañía de Jesús en China: entre evangelización y mediación cultural - Corsi, Elisabetta (El Colegio de México, 2008)
This essay explores the cultural dimension of the Jesuit missionary experience in China during the early modern period while focusing on the particular relationship between evangelization and writing. Jesuit missionaries identified with Chinese intelligentsia by means of their cultural civility and managed to dialogue with them on the basis of book and art collecting, exegesis and bricolage. Defining themselves as “European literati”, the Jesuits showed an intellectual affinity with the Chinese wenren 文 人. Books represent the most significant aspect of the encounter between these two human groups. While interacting with Chinese political and intellectual elite, the Jesuits tried to implement an educational programme modelled on the collegia run by the Society around Europe. The project eventually failed but, by producing books for and about China, the Jesuits contributed to inserting this country within a universal network of circulation of knowledge.